Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Stres Kerja Pada Karyawan PT. Kereta Api Indonesia (Persero) Divisi Regional IV Tanjungkarang - Mega Selly Ananda; Muhammad Wadud; Susi Handayani (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze the effects of workload and work environment on work stress on employees of PT Kereta Api Indonesia Regional Division IV Tanjungkarang. Data of 68 respondents were collected through observation and questionnaires. This study implemented the multiple linear regression method to analyze data. The results unveil that the workload and work environment both partially and simultaneously have significant effects on work stress. This insight can provide benefits for PT Kereta Api Indonesia, Regional Division IV Tanjungkarang. To reduce work stress, the leader of this state-owned company should consider the workload and work environment factors.